All‐Optical Modulation with Dielectric Nanoantennas: Multiresonant Control and Ultrafast Spatial Inhomogeneities. Issue 7 (7th May 2021) - Mazzanti, Andrea; Pogna, Eva Arianna Aurelia; Ghirardini, Lavinia; Celebrano, Michele; Schirato, Andrea; Marino, Giuseppe; Lemaítre, Aristide; Finazzi, Marco; De Angelis, Costantino; Leo, Giuseppe; Cerullo, Giulio; Della Valle, Giuseppe
Abstract : The transient optical response of multiresonant all‐dielectric nanoantennas via a combination of broadband ultrafast reflectivity experiments and nonlinear optics nanoscale modeling is studied. Ultrafast all‐optical control of the reflectivity is demonstrated in variably sized Al .18 Ga .82 As nanoantennas over four distinct Mie resonances (including Fano‐like resonances), spanning a broad spectral range, from the red to the near‐infrared. A spatially inhomogeneous dynamical model, which accounts for diffusion of the photogenerated carriers inside the semiconductor, is introduced and exploited to isolate the physical phenomena leading to the overall transient response, namely, Drude plasma formation and Pauli blocking following band filling and thermo‐optical effect. The results pave the way to the development of multiwavelength all‐optically reconfigurable filters for next‐generation ultrafast add/drop multiplexing. Abstract : All‐dielectric nanoantennas enable to control light fields via excitation of Mie resonances inducing ultrafast all‐optical reflectivity switching. Herein, combining inhomogeneous modeling of the photoexcited charge‐carrier dynamics and ultrafast pump‐probe spectroscopy experiments, the capability of simultaneous modulation of multiple geometrically tunable resonances in the visible and near‐infrared ranges is demonstrated.